Social Equality in a Multi - Religious Society: A Plea for Uniform Civil Code - Deyadoss, T S (Journal of Dharma, 1986)
Democracy is a mere aspiration in the absence of social equality. The concept as such is of no vital significance to our people unless it serves as a means to bring about a change in the socio-economic structure of the community to cherish the ideal of social equality enshrined in the Indian Constitution.